PENGADAAN TANAH UNTUK PEMBANGUNAN PERUMAHAN DI KOTA PALEMBANG - Endy Agustian (Jurnal Tekno Global, 2018)
Residential development in Palembang city is not a simple problem, because residential development need  always grows and population growth increases every year,  but the supply of land for residential development is limited. The research shows that residential developers have noticed the three factors of land provision for residential development. Based on the physical aspect, the wide area of residential is 4 hectare, and land designation status  is garden soil. The easy access and appropriateness  to the RTRW are the considerations of developers for building the residence. Based on the institutional aspect, the status of land rights is property rights by way of purchase. Moreover, land supply through land bank is assessed helping the residential developer. Local governments sometimes help the developers, but the developers have difficulty in particular section permits the acquisition of development principles at a location due to government bureaucracy and complex rule. Based on the economic aspect, land prices are cheap and profitable and they become the reasons for choosing the location of residential developers.  The price of land per meter2 at the time of purchase was relatively high, indicating the residential developers in Palembang city are very effective in raising the economic of land value. Of the three aspects, the economy aspect is prioritized by residential developers, because residential developers as enterpreneurs have an orientation to get the profit.Keywords: Development, Residential Developer